Exploring perceived autonomy support and emotions in university tennis courses. Issue 1 (2nd January 2021) - Simonton, Kelly L.; Solmon, Melinda A.; Garn, Alex C.
Abstract : Using the control-value theory of achievement emotions (CVTAE) as a framework, this study investigated relationships among students' perceived autonomy support, appraisals of control and value, and achievement emotions. Participants were students ( N  = 268) enrolled in a university physical education (UPE) class. They completed validated questionnaires measuring the major constructs within CVTAE including perceptions of the learning environment (autonomy support), control–value beliefs, and achievement emotions (enjoyment and boredom). Hypothesised relationships among the constructs were investigated using structural equation modelling. Autonomy support shared significant relationships with control and value beliefs. Also, control and value beliefs shared direct positive relationships with enjoyment and negatively with boredom. Indirect positive relationships were found from autonomy support to enjoyment and negatively to boredom through value and control as proposed by CVTAE. Overall, 47% of the variance was explained for enjoyment and 41% of boredom. CVTAE is an effective framework to investigate the emotional experiences of participants in UPE settings. Student emotions are important motivation outcomes and represent mechanisms that can potentially help explain outcomes such as volitional physical activity. Findings support the conclusion that perceptions of autonomy support relate to student appraisals of value and control, which in turn relate to higher positive and lower negative achievement emotions. Autonomy-supportive learning environments that provide students with choices, self-pacing, and individualised success can increase attributions of student control. The findings also contribute to a growing body of evidence that demonstrates the importance of students' value toward PE.